Workshop Pengembangan Bisnis Melalui Media Elektronik Berbasis Sosio-Technopreneur Terhadap Usaha Desa Dengan Produk Es Cream Desa Wilayut - Abdul Hafidz Rosydi Fuady; Amaris Evania Putri; Laila Badriyah; Eli Masnawati; Eli Retnowati; Didit Darmawan; Rahayu Mardikaningsih (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The objectives of this community service (PKM) are (1) Increasing the entrepreneurial capacity building of UPPKA Kelut Makmur (Klagen-Wilayut Makmur) cadres in Wilayut Village, (2) UPPKA Kelut Makmur cadres have the provision of soft skills and hard skills to carry out businesses with competitive advantages, (3) Ice Cream Products